PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS IV SD NEGERI 002 KIYAP JAYA KECAMATAN BANDAR SEI KIJANG - Neneng Kurniasih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes SDN PAI 002 Kiyap Jaya.It dibuktika with the acquisition value of the average student in the amount of 65 to 50% ofstudents completeness. This research is a class act. This study was conducted in two cycles.The data used in this study is the activity data and the teacher and student learning outcomesPAI. Based on the research results, direct learners models to improve learning outcomes.This result is evidenced by: (a) the activities of teachers has increased in each cycle, the firstcycle of the first meeting activity for teachers to get a score of 12 (48.00%) with less category,the first cycle II meeting obtain 17 (68.00%) with category enough, the second cycle ofmeetings I obtain a score of 20 (80.00%) in both categories. In the second cycle II meetingobtain a score of 23 (92.00%) with a very good category. And activities of students hasincreased at a meeting I cycle I obtained a score of 11 (44.00%) with less category, thesecond meeting of the second cycle obtain a score of 16 (64.00%) with enough categories, thefirst meeting of the second cycle obtain a score of 19 ( 76.005%) with both categories. And atthe second meeting of the second cycle obtain a score of 22 (88.00%) with a frightening goodcategory; and (b) learning outcomes PAI increased. In preliminary data the average value ofstudents is 65 to 50% the percentage of completeness, in the first cycle to obtain an averagevalue of 69.25 with the percentage of completeness 70% and the second cycle obtain anaverage value of 74.5 with the percentage of completeness of 85%.